농촌여성노인의 정신건강 증진 목적 농장방문형 치유농업 효과 파일럿 연구 - 김용현; 이신자; 허무룡; Yong Hyun Kim; Shin Ja Lee; Moo Ryong Huh (농업생명과학연구, 2024)
본 연구는 농촌에 거주하는 여성 노인을 대상으로 농장방문형 치유농업 프로그램의 효과를 확인하고자 실시한 연구이다. 대상자에게 실시된 치유농업 프로그램은 2023년 6월 22일부터 9월 14일까지 주1회, 회당 3시간씩, 총 12회기로 구성되었다. 매 활동시 대상자들이 치유농장에 방문하여 다양한 원예활동과 농장 내 텃밭 정원을 가꾸는 활동을 실시하였다. 참여대상은 평균 연령 75.38세의 여성 노인 8명이었으며, 치유농업 프로그램 참여에 따른 대상자들의 정신건강 변화를 확인하고자 삶의 만족도, 고독감, 사회적지지 평가를 총 4회(사전, 4회차, 8회차, 12회차) 실시하였다. 조사 결과는 IBM SPSS 25 통계 패키지를 이용하여 빈도분석, 기술통계, Friedman 검정을 실시하여 분석하였다. 그 결과 프로그램 진행에 따라 전반적으로 대상자들의 정신건강이 증진된 것으로 확인되었으며, 특히 삶의 만족도와 사회적지지는 통계적으로 유의미한 수준으로 변화된 것을 확인 할 수 있었다. This preliminary study was conducted to confirm the effectiveness of a farm visit-type agro-healing program targeting older women living in rural areas. This program, implemented for the subjects, consisted of 12 sessions, 3 hours per session, once a week from June 22 to September 14, 2023. During each activity, the subjects visited the healing farm, participating in various horticultural activities and tending to the farm's vegetable garden. The participants were 8 older women with an average age of 75.38 years. To confirm changes in the subjects' mental health following participation in the agro-healing program, life satisfaction, loneliness, and social support assessments were conducted a total of 4 times (preliminary, 4th, 8th, and 12th rounds). The research results were analyzed by performing frequency analysis, descriptive statistics, and Friedman tests using the IBM SPSS 25 statistical package. As a result, it was confirmed that the overall mental health of the subjects improved as the program progressed, and in particular, life satisfaction and social support were confirmed to have changed at a statistically significant level.